PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP KEMAMPUAN LITERASI LINGKUNGAN PADA SISWA SMA YPK 1 EBENHAEZER KOTA SORONG - Irene Blesia; Jaharudin Jaharudin; Sutardi Sutardi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The purpose of this study was to determine the effect of the Project-Based Learning (PBL) model on the environmental literacy skills of students at YPK Ebenhaezer High School in Sorong City. The type and design of the study was pre-experimental, conducted in the odd semester of the 2024-2025 academic year. The number of participants in the study was 14 students. Data collection techniques used observation, questionnaires, and documentation. Data analysis used normality and validity tests. The results showed that the independent sample t-test analysis indicated that tcount > ttable and the significance value was 0.00 < 0.05. Therefore, it can be concluded that H0 is rejected and HA is accepted because there is an effect of the Project-Based Learning (PBL) model on the environmental literacy skills of students at YPK 1 Ebenhaezer High School in Sorong City.